Selected implications of negative externalities – on the example of the Polish energy sector - Mariusz Kudełko; Małgorzata Wejer (Managerial Economics)
The aim of this paper is to present selected issues of the effective allocation of resources and its function in optimal decision-making processes. The authors focus on the economic consequences of market failure in the case of external effects – both positive and negative. It has been characterized from the theoretical perspective by illustrating the economic implications of this situation for producers (producers surplus), consumers (consumer surplus), and the environment (external costs and beneﬁts). This paper shines a light on effective levels of production, the subsidies to producers (in the case of positive externalities), or correcting tax (in the case of negative externalities). Moreover, the decision rules that are used in the cost-beneﬁt analysis (a method supporting the decision-making process undertaken by both private entities and public authorities) are given. There are speciﬁc examples of its application in order to achieve allocative efﬁciency. An exception of its use is to achieve cost efﬁciency, which does not ensure that a project, program, or policy is socially optimal and desirable. The second part of this paper includes theoretical implications of market failure. The results of the authors’ mathematical model that is used to optimize long-term energy sector development are presented. The importance of the presented results is that they reﬂect development of the Polish energy sector, both from the private and public viewpoint, taking into account the adverse effects caused by the emission of gaseous pollutants. Consumer and producer surpluses were the bases to estimate costs and beneﬁts of change in the social welfare. It has been proven that the use of private welfare criterion is incorrect. The internalization of external costs (which means including them in decision-making criterion, signiﬁcantly – i.e., 24%) increases the level of social welfare achieved on the scale of the whole Polish energy sector.